1994
DOI: 10.1002/bms.1200230705
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and differentiation of diglycosyl flavonoids by positive ion fast atom bombardment and tandem mass spectrometry

Abstract: This study shows that fast atom bombardment (FAB) in combination with collisional activation and tandem mass spectrometric techniques is useful for the characterization of, and the differentiation between, O-diglycosyl, O-C-diglycosyl and di-C-glycosyl flavonoids. A quick differentiation between the three types of glycosyl flavonoids is possible by simply examining FAB mass spectra. Low-energy product ion spectra of [M+H]+ ions have been used for determining the carbohydrate sequence in O-diglycosyl flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 10 publications
7
83
0
Order By: Relevance
“…With regard to collisional-induced dissociation, both high-and low-energy CID has been evaluated on instruments (1) and (2). For details about the experimental conditions reference is made to our original articles [5][6][7][8][9][10]. Experimental conditions are only given below for experiments in the negative ion mode, which were performed on instrument (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to collisional-induced dissociation, both high-and low-energy CID has been evaluated on instruments (1) and (2). For details about the experimental conditions reference is made to our original articles [5][6][7][8][9][10]. Experimental conditions are only given below for experiments in the negative ion mode, which were performed on instrument (3).…”
Section: Methodsmentioning
confidence: 99%
“…During the last several years our research at the University of Antwerp has focused on the structural analysis of O-, C-and O,C-diglycosides isolated from medicinal plants using fast atom bombardment (FAB) or electrospray (ES) ionization in combination with collision-induced dissociation (CID) and tandem mass spectrometry (MS/MS) [5][6][7][8][9][10]. In this article we will review various tandem mass spectral approaches to the structural characterization of flavonoid glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…MS/MS in the negative ion mode using an ion trap instrument, 11 and CID using ion trap, 12 triple quadrupole 13 or magnetic sector 14 spectrometers all revealed differences in the fragmentation patterns between schaftoside and isoschaftoside sufficient to allow their differentiation and a positive ion method using FAB-CID has also been described. 15 According to such reports, 11 preferential fragmentation is of the sugar moiety at the 6-C rather than the 8-C position. In the present study it was observed that the unequivocal distinction of schaftoside and isoschaftoside was possible through comparison of the differences in the relative abundance of fragments at m/z 475 ( .…”
Section: 8-di-c-glycosylflavonesmentioning
confidence: 99%
“…With the development of mass spectrometry, many ionization methods have been used to characterize flavonoid compounds, such as EI, 17,18 CI, 19 and FAB. [20][21][22][23] Since the discovery of soft ionization, matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) 24 and electrospray ionization (ESI) [25][26][27][28][29][30] have also been applied to the analysis of flavonoids. Because ESI-MS has a potential to generate ions directly from the liquid phase, which means that it is possible to provide molecule structure information in a solution environment, it has become a very popular analytical method to analyze the compound structure in solution.…”
Section: Introductionmentioning
confidence: 99%